دور إدارة المعرفة في دعم قرارت المسيريين دراسة حالة بمؤسسة اتصالات الجزائر سوق أهراس - نائلة بوكحيلي (My University, 2021)
This study aims to know the role of knowledge management in supporting the decisions of managers in the Algeria Telecom Corporation in the state of Souk Ahras. We have touched on a theoretical study that included all the elements related to the study. To explore this topic, we conducted a study using questionnaires, which they distributed to the workers of the Algeria Telecom Company and we used Statistical treatment of the results, and we have reached a number of theoretical and field results, the most important of which are: Knowledge management has a major role in decision-making, since the latter requires knowledge, understanding, careful and in-depth study of current events, and the ability to anticipate the future. Therefore, it can be said that knowledge management It is the backbone for decision making. ...................................................................... تهدف هذه الدراسة الى معرفة دور إدارة المعرفة في دعم قرارات المسيريين في مؤسسة اتصالات الجزائر لولاية سوق اهراس و قد تطرقنا الى دراسة نظرية تضمنت جميع العناصر التي تتعلق بالدراسة و لاسقاط هذا الموضوع قمنا بدراسة على طريقة الاستبانات ، قمن بتوزيع على عمال شركة اتصالات الجزائر و استخدمنا المعالجة الاحصائية لنتائج و قد توصلنا الى جملة من النتائج النظرية و الميدانية اهمها : ان لإدارة المعرفة الدور الكبير في اتخاذ القرارات كون ان هذا الاخير يتطلب المعرفة و الفهم و الدراسة الدقيقة المتعمقة للاحداث الحالية ، و القدرة على توقع المستقبلدية و بالتالي يمكن القول ان ادارة المعرفة تعد بمثتبة العمود الفقري لاتخاذ القرار.